Administrative Responsibility for Driving While Intoxicated in the Legislation of the Cis Countries: Comparative Legal Analysis - V. Rumyantsev, Nikolay; Shamsunov, SalikhKh.; V. Zhuravlev, Vladimir (International Journal of Psychosocial Rehabilitation, 2020)
Relevance of the study: The relevance of the problem under study is due to the need to improve the road safety system and the lack of elaboration and fragmentation of normative legal acts regulating the procedure and grounds for bringing to justice drivers driving a vehicle while intoxicated. Purpose of the study: The purpose of the article is to study the normative legal acts of the members of the Community of Independent States (CIS), conduct their comparative analysis, and develop proposals for improving the mechanism of measures of the institute of state coercion and their testing. Research methods: The leading method of this problem study is a comparative legal analysis of legislative acts regulating administrative responsibility for violation of traffic rules. Research results: The article presents proposals aimed at improving the national legislation on administrative offenses. Practical significance: The results of the study allow us to develop an optimal design of the administrative and legal norm that establishes responsibility for driving while intoxicated, qualifying signs that determine the increased responsibility of drivers